PENGARUH LATIHAN UNDER THE BASKET SHOT TERHADAP KETERAMPILAN SHOOTING PADA PERMAINAN BOLA BASKET PUTRA CLUB ANGKASA JUNIOR TUALANG KABUPATEN SIAK - Yunita Sapriani; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem with this research it still a lack of skil shooting at the time of two points on the basketball game is the son of Club Angkasa Junior Tualang Kabupaten Siak. Based on the issue of the researchers provide training under the basketball shot. This study aims to find out if there is the influence of training under the basketball shot of skills shooting on the basket ball game is the shon of Club Angkasa Junior Tualang Kabupaten Siak, so that during a two points were shooting. The research is experimental treatment (Experimental), with a population , the data in this research is the entire population of 12 people. The instruments used in this research is to test shot 30 seconds, which aims to measureskills of the bass. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the effect under the basketball shot exercises to the skill of shooting. Based on the analysis of statistical data, there are an average Pree-test of 8,83 and an average post-test 11,08, then the data is normal with an increase of 2,25. Based on t test analysis produces Ttabel Thitung of 4,94 and 1,796, meaning Thitung> Ttabel. Thus, there Effect of under the basket shot training to the skill of shooting the basketball game on male of Club Angkasa Junior Tualang Kabupaten Siak.Key Word: Under The Basket Shot, The Skill Shooting